Pengaruh Citra Toko Dan Lokasi Terhadap Keputusan Pembelian : (Survei Pada Konsumen Toko Puskud Jabar Rajapolah Tasikmalaya) - Alidza Zahara (CV. ULIL ALBAB CORP, 2022)
The purpose of this study was to determine and analyze Store Image, Location and Consumer Purchase Decisions at PUSKUD Jabar Rajapolah Stores. The research method used in this study is causality through a survey approach. With a research sample of 100 consumers PUSKUD Jabar Rajapolah Shop. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 25.0. The results showed that partially the store's image have a significant effect on purchasing decisions, the location of the store had a significant influence on purchasing decisions. Simultaneously store image and store location have a significant influence on purchasing decisions at PUSKUD Jabar Rajapolah Stores.